Analysis of A Systematic Literature Review on Dyslexia in Children - Arifin, Fatkhul; Supena, Asep; Fauzan, Fauzan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to find the main themes and research categories on reading difficulties (Diselectia). For the data taken to fulfill the purpose of this study, the authors searched several relevant sources from Google Scholar and Scopus (SAGE et al. & Francis). Articles were determined using four combinations of keywords; reports were included in the data set, and the researcher applied a systematic literature review method. Pieces that will become research sources are limited to the last six years. The total number of articles reviewed was 921 from different sources, namely Springer, Elsevier, SAGE, Eric, and Taylor & Francis. Articles were re-selected according to indicators, and then 194 articles were obtained. The dominant research methodology of the articles reviewed is qualitative. The four main themes revealed from the qualitative content analysis are dyslexia, causes of dyslexia, cases of dyslexia, and solutions to overcome dyslexia. Articles are filtered from topic descriptions, eligibility criteria, and search strategies. The cause of dyslexia can be due to developmental errors during pregnancy or other factors such as physical defects or habits that the child has. The solution offered by the teacher is to use several methods and learning media that are appropriate to the child's condition.